Pharmacy Technicians' Contribution to Counselling at Community Pharmacies in Denmark - Mira El-Souri; Rikke Nørgaard Hansen; Ann Moon Raagaard; Birthe Søndergaard; Charlotte Rossing (MDPI AG, 2020)
(1) Background: pharmacy technicians are the largest group of staff at Danish community pharmacies and play a vital role in counselling customers on prescription medication, over-the-counter (OTC) medication and non-medical products. This is the first study carried out to specifically analyse how they contribute to counselling and identification of drug-related problems (DRPs) at Danish community pharmacies. (2) Methods: seventy-six pharmacy technicians from 38 community pharmacies registered data on all of their customer visits for five days, over a four-week period, between January and March 2019. Data were analysed in SPSS version 24. (3) Results: 58.9% of all registered customers (n = 10,417) received counselling. They identified DRPs for 15.8% of all registered customers (n = 2800). Counselling by pharmacy technicians solved, or partially solved, problems for 70.4% of customers with DRPs. Pharmacy technicians estimated that 25.2% of customers receiving counselling (n = 2621) were saved a visit to the general practitioner (GP). (4) Conclusions: as community pharmacists get more involved in complex services, it would be necessary to expand the roles of pharmacy technicians. Pharmacy technicians contribute to medication safety via counselling, and identifying and handling DRPs for all customers. This study documents the role of pharmacy technicians in customer counselling at Danish community pharmacies. It provides evidence to researchers and policy makers to support discussions on the future role of pharmacy technicians at community pharmacies.